2009
DOI: 10.1007/978-3-642-02498-6_24
|View full text |Cite
|
Sign up to set email alerts
|

MRI Tissue Classification and Bias Field Estimation Based on Coherent Local Intensity Clustering: A Unified Energy Minimization Framework

Abstract: Abstract. This paper presents a new energy minimization method for simultaneous tissue classification and bias field estimation of magnetic resonance (MR) images. We first derive an important characteristic of local image intensitiesthe intensities of different tissues within a neighborhood form separable clusters, and the center of each cluster can be well approximated by the product of the bias within the neighborhood and a tissue-dependent constant. We then introduce a coherent local intensity clustering (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 23 publications
(31 reference statements)
0
80
0
1
Order By: Relevance
“…Most of the current algorithms were developed for brain imaging. [21][22][23] The implementation of these algorithms for breast MRI can be more challenging as a result of the increased FOV. Although N3 algorithm has been considered as an optimal method for intensity inhomogeneity correction by a recent review paper, 17 a study on clinical breast images has shown that using N3 alone may still have problems in breast images, which cannot allow an accurate segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the current algorithms were developed for brain imaging. [21][22][23] The implementation of these algorithms for breast MRI can be more challenging as a result of the increased FOV. Although N3 algorithm has been considered as an optimal method for intensity inhomogeneity correction by a recent review paper, 17 a study on clinical breast images has shown that using N3 alone may still have problems in breast images, which cannot allow an accurate segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…More details of the CLIC method can be found in the report by Li et al 23 To evaluate the effect of bias field, we compared the breast segmentation results from three studies: (a) FCM clustering on raw images; (b) CLIC clustering on raw images; and (c) FCM clustering on bias-field-corrected images. In study (a), Basic FCM algorithm was applied to the raw MRI images of the postmortem breast samples.…”
Section: B Bias Field Correction and Tissue Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the intensity of the same tissue should always be similar in one image and not vary with the location of the tissue. For many automated analysis techniques such as segmentation, classification and registration, this property can facilitate their procedures and make their results reasonable (C. Li, Li, Kao, & Xu, 2009;C. Li, Xu, Anderson, & Gore, 2009;Xu, Wan, & Bian, 2013;C.…”
Section: Introductionmentioning
confidence: 99%